Il foro della residenza abituale del coniuge nel Regolamento (CE) N° 2201/2003: note a margine delle prime pronunce italiane - Campiglio, Cristina (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
Concerning matrimonial matter, the Article 3 of Regulation (EC) n° 2201/2003 lists numerous alternative jurisdiction titles, prevailingly based on the habitual residence of either or both spouses. In international practice the notion of habitual residence is traditionally atechnical, of factual nature, and typically recalls the element of stability in residence, whereas that stability must be also intentional is uncertain. Two recent decisions by the Italian Corte di Cassazione about forum actoris leave intentionality of stable residence apart. By contrast, the French Cour de Cassation gives relevance to the volontary element. The issue of the weight to be given to the intentionality element should be addressed by the Court of Justice.
Keywords: Jurisdiction; Regulation 2201/2003; habitual residence; interpretation